Young bride: an analysis on the application of the minimum age of marriage in Malaysia - Md Hashim, Noraini; Che Soh @ Yusoff, Roslina (2013)
Parents choose to marry off their daughters early for a number of reasons. Poor families may regard a young girl as an economic burden and her marriage as a necessary survival strategy for her family. They may think that child marriage offers protection for their daughter from the dangers of sexual assault, or more generally, offers the care of a male guardian. Young bride may also be seen as a strategy to avoid girls becoming pregnant outside marriage. In Islam, although there is no clear injunction under the Quranic verse or Hadith (prophetic tradition) specifying minimum age of marriage, the Malaysian government has taken step to specify minimum age of marriage as a preventive measure to protect the young bride under the provision of Islamic Family Law Act and Enactments for the Muslims. There are many complex range of issues relating to young bride that need to be taken into account when assessing a provision on minimum age of marriage which more or less option giving. For instance whether or not there is minimum age of marriage; whether the marriage of this young bride legal, if so, with whose consent and under what conditions; whether or not ijbar (compulsion in marriage) is permissible and if so, who is recognised as having power whether or not the marriage is illegal and subject to penalties. This paper is to enlighten as to the issue of young bride in Malaysia by analyzing the relevant provision under the Islamic Family Law Federal Territories Act 1984 (Act 303) and decided under the Shariah Court.